O trabalho com o gênero resenha crítica nas aulas de língua portuguesa: a contribuição das metodologias ativas - Alves, Deyse Souza (2023)
We know of the many issues both Portuguese language teachers and students face when a proposed text writing activity aims at materializing a speech genre, such as critical reviews, editorial articles, among others. We also understand that the work with these genres should no longer display a "simulacrum" character, as pointed out by Bezerra (2020). Based on this knowledge, this paper aims at investigating how a didactic proposal of Portuguese language teaching, based on the usage of active methodologies, can aid students of a public school currently in Year 8 to understand and write critical reviews. This genre was chosen because we believe that it is present in the students's everyday lives and, thus, it is necessary for them to have a deeper understanding of its specific attributes, as underlined by BNCC, the National Common Curriculum Base (BRASIL, 2018). Furthermore, this genre has argumentative traits, and we believe that arguing is innate to human beings, as maintained by Koch and Elias (2020). Hence the relevance of this work, which presents, in its didactic proposal, the possibility of participating-students coming into contact with varied examples of critical reviews with the intention that they develop knowledge of this genre and improve their argumentative abilities during the writing of their own critical reviews. For this, we based ourselves in the theories of Bakhtin (1997; 2016), Abreu (2009), Koch and Elias (2020), Geraldi (1997; 2010), Machado, Lousada, Abreu-Tardelli (2004), Marcuschi (2001; 2008), Moran (2018), Perelman and Olbrechts-Tyteca (2014), among other authors who address this study's subject. Methodologically, we adopted Thiollent's (1996) action research, Michel's (2009) qualitative approach, and, through Bortoni-Ricardo's (2008) interpretative methodology, we interpreted the responses obtained. Our didactic proposal was inspired by Rojo and Moura (2012), a travelable prototype that can be adapted by other teachers according to the realities of the classes it will be applied to. During the eleven meetings suggested in the proposal, we noticed that the participating students understood and wrote pieces of the critical review genre, displaying its constituting, thematic, and stylistic elements particular to the genre. The pieces written circulated amongst the real community of the school where the study took place, as suggested by Geraldi (2010), who advocates the importance of writing practices based on a universe as close to the students's reality as possible.